REGIONAL FEATURES SOCIO-CULTURAL SPACE OF THE MOUNTAIN SCHOOL - Chervinska, Inna; Chervinskyi, Andrii (Mountain School of Ukrainian Carpaty, 2019)
In the article the regional peculiarities and educational potential of socio-cultural space of the mountain school of the Carpathian region are methodologically substantiated and defined. The authors reveal the essence of socio-cultural space as one of the constituents of shaping the space of a certain region and emphasize that the definition of "space" is the most suitable for describing phenomena that have qualitative characteristics of extent, meaningfulness and representation. The purpose of the study is to describe the regional features of socio-cultural space of the mountain school in the context of ensuring sustainable development of Ukraine. The leading objectives of the study include: isolation of educational, socio-economic and other problems of mountain regions; identifying ways to improve the efficiency and quality of educational services to educational institutions in mountain regions; increase of the level of socio-cultural literacy, formation of ecological consciousness and critical thinking of inhabitants of mountain areas; disclosure of regional peculiarities of socio-cultural space of the mountain school. Research methodology includes general scientific research methods: comparison and analogy, analysis and synthesis, deduction and induction, methods of abstraction, classification, systematization, historical method. It is pointed out that the features of the regions of Ukraine are revealed as relatively independent units, formed on the basis and due to the interaction of territorial and natural conditions, common history, culture and language, demographic, social and economic indicators.